2019
DOI: 10.14500/aro.10535
|View full text |Cite
|
Sign up to set email alerts
|

Aqra Anticline: A Growing Structure in the Iraqi Kurdistan Region

Abstract: Aqra Anticline is a double plunging anticline, oriented NW–SE with a steep southwestern limb and even overturned. Geomorphological features are interpreted using satellite images, as a result, it was found that the anticline shows clear geomorphological and structural features which indicate the lateral growth of the anticline. Among those features are water gaps, wind gaps, forked-shaped valleys, curved valleys, inclined valleys and dislocated and abandoned alluvial fans. Some of the vague interpreted feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…They used the same geomorphological and structural forms that have been used in this study. Ghafur et al (2019) conducted a tectonic-geomorphological study on the Aqra anticline, confirming its lateral growth using geomorphological and structural forms. Finally, in the latest study conducted by Sissakian et al (2020), the authors studied the lateral growth of the Handreen, Zozik, and Tanoun anticlines in the Kurdistan Region of Iraq, relying on geomorphological features.…”
Section: Previous Studiesmentioning
confidence: 91%
“…They used the same geomorphological and structural forms that have been used in this study. Ghafur et al (2019) conducted a tectonic-geomorphological study on the Aqra anticline, confirming its lateral growth using geomorphological and structural forms. Finally, in the latest study conducted by Sissakian et al (2020), the authors studied the lateral growth of the Handreen, Zozik, and Tanoun anticlines in the Kurdistan Region of Iraq, relying on geomorphological features.…”
Section: Previous Studiesmentioning
confidence: 91%
“…3). Ghafur et al (2019) studied the Aqra anticline that is located NW of the Shakrook anticline and showed that the Aqra anticline is laterally growing. They used different geomorphological and structural indications to confirm the growth of the anticline.…”
Section: Fig 1 Satellite Image Showing Shakrook Anticline With Locations Of the Presented Images In The Text With Their Serial Numbersmentioning
confidence: 99%
“…The Shakrook anticline exhibits very complicated structural form that is quite different from the existing anticlines in near surroundings, and it is oriented in a NW -SE trend. The Iraqi Kurdistan Region (IKR) is considered as tectonically an active area, it forms the northeastern part of the Arabian Plate (Berberian, 1993, Blanc et al, 2003, Bennett et al, 2005, Ramsey et al, 2008, Ghafur et al, 2019, Sissakian et al, 2020. The anticlines in the region are developed due to collision of the Arabian Plate with the Eurasian (Iranian) Plate, forming a convergent tectonic plate boundary (Alavi, 2004, Allen et al, 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqra and Bakhme formations are consist of reef limestone, Aqra Fm. is locally dolomitized, siliceous, and impregnated with bitumen, Bakhme is secondary dolomitized, the Pila Spi Formation comprises well-bedded, bituminous, chalky, and crystalline limestone, with bands of white, chalky marl, and with chert nodules towards the top (Jassim & Goff, 2006), the formation spreads on both sides of the Aqra fold as a belt with a thickness of 85 m and a widespread, especially in the northwest of the fold depression (Ghafur et al, 2019). The Fatha Formation components are various, it comprises anhydrite, gypsum, and salt inter bedded with limestone and marl, the formation appears in the Aqra fold, as it follows the formation of Pila Spi in an unconformity manner (Aqrawi, 1990).…”
Section: Stratigraphy Of the Study Areamentioning
confidence: 99%